Random walk Monte Carlo simulation of diffusive ferromagnetic Ising spin under Lennard-Jones interaction - Jutarop Reungyos (2018)
This work investigated properties of diffusive magnetic particles. Random walk Monte Carlo method was used to simulate the Ising spin diffusing and flipping to examine the properties of the system. The Ising spins interact among themselves via Lennard-Jones interaction. Metropolis algorithm was employed to update spins configuration on the continuous space. The volume of Ising spins, magnetization and magnetic susceptibility, were investigated as functions of temperature, number of Ising spins in the system and simulation time. It was found that, at low temperatures, the Ising spins tend to stay close even at long simulation time, where finite magnetization was found suggesting the ferromagnetic preference. However, at high temperatures, paramagnetic behavior reveals as ferromagnetic interaction ceases with time passing. This is due to role of spin diffusing which causes the spins to disperse and hence ferromagnetic interaction among spins reduces. © (2013) Trans Tech Publications, Switzerland.